Bimetallic zeolitic imidazolate framework-derived substrate-free anode with superior cyclability for high-capacity lithium-ion batteries. (20th March 2021) - Joshi, Bhavana; Samuel, Edmund; Kim, Yong-il; Periyasami, Govindasami; Rahaman, Mostafizur; Yoon, Sam S.
Abstract: Freestanding carbon nanofibers loaded with bimetallic hollow nanocage structures were synthesized. The nanocages inherited the rhombic dodecahedral morphology of the zeolitic imidazolate framework (ZIF) precursors, ZIF-8 and ZIF-67. As anode materials for lithium-ion batteries (LIBs), the bimetallic nanocage-loaded freestanding carbon nanofibers effectively buffered volume expansions and alleviated pulverization through their different reduction and oxidation potentials. The higher capacities of the composite anodes arose via the formation of the Li x Zn alloy and Li2 O by Zn and Co ions, respectively, and the enhanced conductivity conferred by the carbon nanofibers. A synergistic effect of the composite components toward the strong electrochemical performance (688 mA h·g −1 at 1200 mA·g −1 ) of the bimetallic nanocage-loaded fibers was demonstrated through the superior long-term stability of the anode (1048 mA h·g −1 after 300 cycles at 100 mA·g −1 ), suggesting that the fabricated anode can be a promising material for use in portable LIBs.